Methods of Measuring Quality in Higher Education - Targaszewska, Marta (Metody pomiaru jakości kształcenia na uczelniach wyższych, 2011)
The paper contains discussion of some methods of the measurement of higher education quality. This article consists of two parts. The first presents concepts of: quality, service quality, and service quality in education. The second part of the paper introduces two selected methods of the measurement of higher education quality: a model of SERVQUAL, and the quality index which can be used to create the rankings of academic institutions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 67-75
Keywords: jakość; edukacja; metoda Servqual; jakość kształcenia; szkolnictwo wyższe; quality; education; Servqual method; quality education; higher education